THE CONTRIBUTION OF HOUSEHOLD MEMBERS TO FISHERMAN INCOME IN PASAR II NATAL VILLAGE NATAL DISTRICTS MANDAILING NATAL REGENCY NORTH SUMATRA PROVINCE - Dodi Firmansyah; Darwis '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in May 2016 in Pasar II Natal Village Natal Districts Mandailing Natal Regency North Sumatra Province. The purpose of the research are to identify the types of business of fisherman household members, to analyze the contribution of household members fisherman and the analyze business profitability cultivated by household members fisherman. The research method was used by survey and the determine of respondents by census. The results of this research indicate that activities performed by fisherman household members in Pasar II Natal Village on the fisheries sector and non fisheries. The contributions of household members fisherman given by the fishermen themselves is relatively high at 69.84%, from the fisherman's wife with a contribution of 14.46% which is low, as well as the children of fishermen with a contribution 25.7% were classified as low. Value business profitability cultivated by household members fisherman both wives and children of fishermen all > 25%, so that the business can be said is already profitable, efficient and feasible to be developed.Keywords : Contribution, Fisherman Household Members, Income